Proceedings of SPE Annual Technical Conference and Exhibition 1994
DOI: 10.2523/28304-ms
|View full text |Cite
|
Sign up to set email alerts
|

Practical Pressure Loss Predictions in Realistic Annular Geometries

Abstract: IA, U.S.A., 2S-28 S9pterIIfMr 1SS4. TM pepw was eelected for prwenteticm by en SPE Progrem Cammti following review of infonnatkm wntelned in en ebstracf aubmitfed by the author(s). Contents of the paper, *~~,~W~~~by tm q Of M*m Ewineefe d are subi@ to .2(mctii by the authof(t+ The meterid, ee pmawwd, does not Mcc3eeriiy reflect MY Ph of t~SockW of -um Entti-. Ss oSkem. w membw'e. Pews weaenfed et SPE mwtinoe em wblect to publketicm review by Editoriel Committees of the Socii dP~E~m. W~bqrntiti ma~&ti-tti~ti.ll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…At 0.7 m/s, the Reynolds number is already well above 2000, and transitional flow effects may have increased the pressure gradient. Haciislamoglu and Cartalos [16] found that the pressure loss reduction due to eccentricity is smaller in the transitional region than both in the laminar and in the turbulent regions. This effect has not been modeled here, which may account for the discrepancy in this region.…”
Section: Circulation Pressure Dropmentioning
confidence: 95%
See 1 more Smart Citation
“…At 0.7 m/s, the Reynolds number is already well above 2000, and transitional flow effects may have increased the pressure gradient. Haciislamoglu and Cartalos [16] found that the pressure loss reduction due to eccentricity is smaller in the transitional region than both in the laminar and in the turbulent regions. This effect has not been modeled here, which may account for the discrepancy in this region.…”
Section: Circulation Pressure Dropmentioning
confidence: 95%
“…between pressure gradient in eccentric and concentric annuli, respectively, where ɛ is eccentricity and κ is the ratio of D i over D o . For turbulent flow the correlation developed by Haciislamoglu and Cartalos [16] for a power-law fluid was used. This fluid was adapted to a yield stress fluid following Kelessidis et al [17], using the flow behavior index n in the correlation.…”
Section: Circulation Pressure Dropmentioning
confidence: 99%
“…Haciislamoglu and Langlinais [12] and Haciislamoglu and Cartalos [13] presented models for pressure loss corrections for eccentric annuli in laminar and turbulent flow. These models are presented in Eqs.…”
Section: Corrections For Eccentricitymentioning
confidence: 99%
“…Additional pressure loss of eccentricity and drill pipe rotation: To calculate circulating loss more accurately, the effects of drill pipe eccentricity and rotation must be considered. The influence coefficient of drill pipe eccentricity is as follows (Haciislamoglu and Cartalos, 1994…”
Section: Mathematical Models Of Additional Pressure Lossmentioning
confidence: 99%